SOCIALIZATION ACTIVITIES ABOUT IMMIGRATION AND IMMIGRATION POLYTECHNIC BY POLTEKIM CADETS AT SMAN 3 TARUNA ANGKASA MADIUN - Respati Triana Putri; Ale Alfero Deputra; Agung Sulistyo Purnomo (Jurnal Abdimas Imigrasi, 2021)
Availability of information on further education after high school is one of the needs of students who have entered the final period of high school. Credibility and detailed information is often not easy to obtain because of the uncontrolled flow of information exchange and unclear data sources. Socialization is the main solution to provide credible and detailed information to students who need it.. The implementation of this socialization activity is a form of community service when the Immigration Polytechnic cadets carry out Field Work Practice activities in the Madiun area, East Java. This socialization activity related to Immigration and the Immigration Polytechnic official school at SMAN 3 Taruna Angkasa Madiun aims to disseminate information related to Immigration and Poltekim. In addition, this activity provides insight and knowledge as well as enthusiasm and motivation to the cadets of Angkasa Madiun. With this socialization activity, it is hoped that the community, especially the younger generation, namely the younger generation of Angkasa Madiun cadets, understand more about immigration and the Immigration Polytechnic.